Multi road shoulder measurement tool / Siti Marlinna Chu Mohd Rizal Chu … [et al] - Mohd Rizal Chu, Siti Marlinna Chu; Alias, Mohd Hanafi; Mat Nawi, Mohamad Amerul; Rajid, Nurul Farrahziana; Md. Nor, Nor Amarlina; Po'a, Ayu Wirdawati; Abdul Rahman, Umi Hani (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Multi Road Shoulder Measurement tool is design to measure the road shoulder cross slope. The type of cross slope of the road shoulder is 2-6%, 4-6%, and 6%. There had been no special tools to measure the shoulder of the road. The authorities had set up levelling instrument to measure road shoulder height. Road conditions will be damaged when the gradient of the road shoulder is not measured correctly. The tools is designed to measure the slope of the road shoulder as stipulated in the JKR specifications easily and more accurately so that problems that often occur on the road can be avoided. Multi road shoulder Measurement Tools will be constructed to measure the slope of the shoulder of the road to be more accurate.